The tribological performances of modified magnesium silicate hydroxide as lubricant additive. (May 2018) - Gao, Kai; Chang, Qiuying; Wang, Bin; Zhou, Ningning; Qing, Tao
Abstract: Modified magnesium silicate hydroxide (MSH) was synthesized by hydrothermal method with magnesium oxide and silica as raw materials, and oleic acid (OA) as the modified agent. The tribological properties of MSH as lubricant additive were studied by the four-ball tests. The tests results show that the MSH-containing oil exhibits better anti-wear properties than the base oil, with the highest rate of wear reduction reaching 55%. In addition, different test conditions, such as load and rotation speed, have an influence on the anti-wear properties of MSH. It is assumed that both physical effects and tribochemistry reactions could contribute to the anti-wear properties of MSH. Highlights: Magnesium silicate hydroxide was synthesized by hydrothermal method. The MSH nanoparticles as additives show great tribological properties. Both physical and tribochemical effects contribute to the anti-wear properties.